UNIVERSALITY AND SPECIFICITY IN THE STUDY OF THE RELATIONSHIP BETWEEN LANGUAGE AND LOGIC - Rakhimova Maftuna Odilovna (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical significance of the categories of universality and specificity in the study of the relationship between language and logic. It explores the interaction between the general logical foundations of language and the national-cultural, semantic, and grammatical features characteristic of particular language systems. The study analyzes the ways in which logical categories are expressed across different languages, as well as the relationship between universal laws of thought and their linguistic realization. Furthermore, it argues that the dialectical unity of universality and specificity constitutes an important methodological principle for understanding the relationship between language and thought.